Optimized high-yield preparation of alkaline-solubilizable crystalline inclusion of the Bacillus thuringiensis Cry4Aa δ-endotoxin expressed in Escherichia coli - Sakdee S. (2023)
The native Cry4Aa δ-endotoxin produced exclusively in Bacillus thuringiensis during sporulation as a ∼130-kDa inactive protoxin is confined within the parasporal crystalline inclusion that dissolves at alkaline pH in the midgut lumen of mosquito larvae. Here, the recombinant Cry4Aa toxin over-expressed in Escherichia coli at 30 °C as an alkaline-solubilizable inclusion was found inevitably lost during isolation from the cell lysate (pH ∼6.5) of which host cells were pre-suspended in distilled water (pH ∼5.5). When 100 mM KH2PO4 (pH 5.0) was used as host cell-suspending buffer, the cell lysate's pH became more acidic (pH 5.5), allowing the expressed protoxin to be entirely retained in the form of crystalline inclusion rather than a soluble form, and thus high-yield recovery of the partially purified inclusion was obtained. Upon dialysis of the alkaline-solubilized protoxin against the KH2PO4 buffer, the protoxin precipitate was efficiently recovered and still exhibited high toxicity to Aedes aegypti mosquito larvae. Additionally, the precipitated protoxin was completely resolubilized in 50 mM Na2CO3 buffer (pH 9.0) and proteolytically processed by trypsin to produce the 65-kDa activated toxin comprising ∼47- and ∼20-kDa fragments. In silico structural analysis suggested that His154, His388, His536 and His572 were involved in a dissolution of the Cry4Aa inclusion at pH 6.5, conceivably through interchain salt bridge breakage. Altogether, such an optimized protocol described herein was effective for the preparation of alkaline-solubilizable inclusions of the recombinant Cry4Aa toxin in large amounts (>25 mg per liter culture) that would pave the way for further structure-function relationship studies of different Cry toxins.